2015
DOI: 10.1021/acs.jnatprod.5b00634
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Indolosesquiterpenoid Xiamycins C–E from a Halophilic Actinomycete

Abstract: New metabolites, xiamycins C-E (1-3), were isolated from a Streptomyces. sp (#HK18) culture inhabiting the topsoil in a Korean solar saltern. The planar structures of the xiamycins C-E were elucidated as carbazole-bearing indolosesquiterpenoids using a combined analysis of NMR, MS, UV, and IR spectroscopic data. The absolute configurations of these new compounds were determined by analyses of NOESY and ECD data. When the xiamycins were tested for inhibitory activity on porcine epidemic diarrhea virus (PEDV), x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…However, the chemistry of actinobacteria in these hypersaline environments had been mostly neglected until the report of Kim et al [30], on the production of saltern amides with the ability to induce apoptosis in human cancer cells, as the first secondary metabolites from a saltern-derived Streptomyces sp. So far, several bioactive compounds such as xiamycins C-E from a halophilic Streptomyces sp., with potent antiviral activity against porcine epidemic diarrhea virus (PEDV) [12] and borrelidins C-E from a saltern-derived halophilic Nocardiopsis sp. with antibacterial activity against S. enteric [14], have been discovered from halophilic actinomycetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the chemistry of actinobacteria in these hypersaline environments had been mostly neglected until the report of Kim et al [30], on the production of saltern amides with the ability to induce apoptosis in human cancer cells, as the first secondary metabolites from a saltern-derived Streptomyces sp. So far, several bioactive compounds such as xiamycins C-E from a halophilic Streptomyces sp., with potent antiviral activity against porcine epidemic diarrhea virus (PEDV) [12] and borrelidins C-E from a saltern-derived halophilic Nocardiopsis sp. with antibacterial activity against S. enteric [14], have been discovered from halophilic actinomycetes.…”
Section: Discussionmentioning
confidence: 99%
“…is increasing number of nonconventional actinomycetes considerably paves the way for the discovery of new bioactive natural products [11,12]. e discovery of novel strains of halophilic actinobacteria seems to be the first and the key step toward obtaining novel bioactive compounds and subsequently to design natural product-based drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Our continuing study of saltern-derived actinomycetes led to the discovery of indolosesquiterpenoids, called xiamycins C–E, from a halophilic Streptomyces sp. Xiamycin D displayed potent antiviral activity against porcine epidemic diarrhea virus (PEDV) [8]. These promising results indicated that saltern-derived actinobacteria can be utilized as prolific sources of bioactive secondary metabolites with pharmaceutical potential, leading us to expand our research program from the common genus Streptomyces to diverse phylogenetic groups in the phylum Actinobacteria that inhabit salterns.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our efforts to discover new bioactive natural products, we have been investigating the chemistry of actinobacteria derived from marine and saline environments including salterns [5,6,7], intertidal zones [8,9,10,11], and deep-sea sediments [12]. In our previous reports, novel bioactive secondary metabolites were mainly identified through the chemical profiling of bacterial secondary metabolites by LC/MS analysis.…”
Section: Introductionmentioning
confidence: 99%